Elite North American soccer performance in thermally challenging environments: An explorative approach to tracking outcomes - Draper, G.; Atkinson, G.; Chesterton, P.; Portas, M.; Wright, A. (Journal of Sports Sciences, 2023)
Aims The physiologic challenges related to performances in hot conditions calls for dedicated consideration when planning athlete training, although complete amelioration of the effects of heat may not be possible. We aimed to quantify within-subject correlations between different measures of environmental temperature and performance changes over multiple elite soccer competitions.